Differental effects of glatamate agonist and D-aspartate on oxytocin release from hypothalamus and posterior pituitary of male rats. - Pampillo, Macarena (2001)
In order to determine whether ionotropic (iGluRs) and metabotropic (mGluRs) glutamate receptor activation modulates oxytocin release in male rats, we investigated the effect of agonists of both types of glutamate receptors on oxytocin release from hypothalamus and posterior pituitary. Kainate and quisqualate (1 mM) increased hypothalamic oxytocin release. Their effects were prevented by selective AMPA/kainate receptor antagonists. NMDA (0.01-1 mM) did not modify hypothalamic oxytocin release. Group I mGluR agonists, such as quisqualate and 3-HPG, significantly increased hypothalamic oxytocin release. These effects were blocked by AIDA (a selective antagonist of group I mGluRs). In the posterior pituitary, oxytocin release was not modified by kainate, quisqualate, trans-ACPD (a broad-spectrum mGluR agonist) and L-SOP (a group III mGluR agonist). However, NMDA (0.1 mM) significantly decreased oxytocin release from posterior pituitary. D-Aspartate significantly increased oxytocin release from the hypothalamus, while it decreased oxytocin release from posterior pituitary. AP-5 (a specific NMDA receptor antagonist) reduced the D-Aspartate effect in the hypothalamus, but not in the posterior pituitary. Our data indicate that the activation of non-NMDA receptors and group I mGluRs stimulates oxytocin release from hypothalamic nuclei, whereas NMDA inhibits oxytocinergic terminals in the posterior pituitary. D-Aspartate also has a dual effect on oxytocin release: stimulatory at the hypothalamus and inhibitory at the posterior pituitary. These results suggest that excitatory amino acids differentially modulate the secretion of oxytocin at the hypothalamic and posterior pituitary levels.